The hydroelectricity consumption and economic growth in Asian countries - evidence using an asymmetric cointegration approach. Issue 37 (8th August 2020) - Tiwari, Aviral Kumar; Olayeni, Richard O.; Chang, Yu-Cheng; Chang, Tsangyao
ABSTRACT: This study examines the four commonly tested hypotheses in hydroelectricity consumption – economic growth literature for 12 Asian countries. Our results from a recently developed hidden cointegration technique uncover rich and significant relationships between negative and positive components of the variables under consideration. In particular, we find evidence to support the neutrality hypothesis in five countries (Bangladesh, Indonesia, Pakistan, Philippines, and Thailand), the growth hypothesis in four countries (India, Japan, South Korea and Taiwan), and both growth and conservation hypotheses in three countries (China, Malaysia, and New Zealand). These findings suggest that appropriate economic policies should be elaborated on the basis of the country's specific hydroelectricity consumption–growth nexus. Finally, our new evidence suggests that the lack of stable relationship between hydroelectricity consumption and economic growth documented in previous studies for some of these countries could be due to the failure to properly account for the nonlinearity property in the data.